BUFFER ZONE IN INDONESIAN TERRITORY TO ANTICIPATE IMPACTS OF NUCLEAR WAR ON KOREAN PENINSULA - Riko FENDIAWAN; Joko PURNOMO; Syafrizal IRFAN; Sumartoni MULKU (Journal of Defense Resources Management)
The nuclear issue on the Korean Peninsula in recent decades is considered to have become one of the serious threats to security and stability in East Asia in particular and the world in general. Being an endless topic of conversation is based on the politics applied by North Korea which makes the international world always alert. Indonesia is directly or indirectly one of the countries that will be affected by the Korean peninsula nuclear war. The impact of radiation from the Korean Peninsula nuclear war affects health impacts, environmental impacts and socioeconomic impacts. Buffer zones as one of the alternative steps to mitigate the impact of nuclear war. The method used in this research is a literature review that refers to the development of political issues between the North Korean and South Korean blocks, the theory of buffer zones that have been applied in warfare and studies of the impact due to nuclear radiation that has occurred. The purpose of this research is to mitigate and minimize the impact of the Korean peninsula nuclear war that will be received by the Indonesian region. From the results of the discussion, it can be concluded that the buffer zone is effective as an anticipation of the threat of nuclear war on the Korean peninsula because it can create a security and preparedness zone for the population and planning for strengthening infrastructure that supports the anticipation of the impact of nuclear war. The results of this study contribute to be used as a basic material for strategies to deal with nuclear war on the Korean peninsula.